Hydrographic and Biogeochemical Profiles of Disco Bay: High-Resolution Nitrogen Cycling Experimental Data - Carolin R Löscher; Isabell Schlangen; Elizabeth Leon-Palmero; Annabell Moser; Peihang Xu; Erik Laursen (PANGAEA, 2025)
This dataset presents high-resolution profiles of hydrographic and biogeochemical parameters, alongside results from incubation experiments and discrete measurements conducted in Disco Bay. Data were collected between August 16th and August 26 in 2022, capturing temporal variations in physical and biogeochemical conditions during this period. Key parameters recorded include temperature, salinity, dissolved oxygen, turbidity, and photosynthetically active radiation (PAR), obtained via a Conductivity-Temperature-Depth (CTD) profiler at varying depths (https://doi.pangaea.de/10.1594/PANGAEA.973563). To complement these measurements, incubation experiments were performed to assess nitrogen fixation rates, primary production, and both the production and consumption of nitrous oxide (N?O) (this dataset). Discrete water samples were also collected for the analysis of nutrients, chlorophyll a (Chl a), and N?O concentrations, enhancing our understanding of nutrient cycling and productivity in the Arctic marine environment. Data collection was conducted aboard the danish military vessel P540. The dataset was collected to investigate spatial and temporal variability in hydrographic properties, nitrogen fixation, and productivity, contributing to research on Arctic ecosystem dynamics and the impacts of climate change. Measurements are provided in .txt format. Each parameter was recorded with precision levels appropriate for capturing the region extquotesingles natural variability, particularly in the vertical profiles of the water column. The dataset is expected to support research on Arctic oceanography and biogeochemistry, with applications for studies on climate change, nutrient cycling, and primary productivity. Standardized CTD and experimental protocols were followed to ensure data quality and consistency for comparability with other oceanographic datasets.